1997
DOI: 10.2307/249498
|View full text |Cite
|
Sign up to set email alerts
|

Personal Computing Acceptance Factors in Small Firms: A Structural Equation Model

Abstract: This study draws upon the technology acceptance model as the theoretical basis and empirical findings for a pragmatic explanation of key factors affecting personal computing acceptance in small firms. The study uses results from a survey of 358 users in small firms in New Zealand to test a structural model examining the hypothesized relationships among the following constructs: intraorganizational factors, extraorganizational factors, perceived ease of use, perceived usefulness, and personal computing acceptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

66
802
9
46

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,184 publications
(923 citation statements)
references
References 71 publications
66
802
9
46
Order By: Relevance
“…It was seen that this effect becomes indirect through perceived benefit over time and with increasing amount of experiences. This thesis was asserted in later studies (Gefen and Straub, 1997;Igbaria et al, 1997). Teo et al (1999) stated that the effect of perceived ease of use on behavioral intention is in direct proportion to technological complexity level.…”
Section: Resultsmentioning
confidence: 95%
“…It was seen that this effect becomes indirect through perceived benefit over time and with increasing amount of experiences. This thesis was asserted in later studies (Gefen and Straub, 1997;Igbaria et al, 1997). Teo et al (1999) stated that the effect of perceived ease of use on behavioral intention is in direct proportion to technological complexity level.…”
Section: Resultsmentioning
confidence: 95%
“…These models have all been recognized in the ISs discipline. Using TAM as an example, abundant studies have been done to test (Davis, 1989(Davis, , 1993Davis et al, 1989;Adams et al, 1992), extend (Venkatesh andDavis, 1996, 2000;Igbaria et al, 1997;Venkatesh, 2000;Viswanath and Davis, 2000), or compare it with other models Mathieson, 1991;Taylor and Todd, 1995b;Dishaw and Strong, 1999;Venkatesh and Davis, 2000). Overall, these theoretical models have contributed to our understanding of user acceptance perceptions and behaviors.…”
Section: Overview Of Prior Literaturementioning
confidence: 99%
“…Igbaria et al (1997) argued that experience might be one of the moderating factors. Subramanian (1994) stated two reasons for the inconsistent PEOU effects.…”
Section: Perceived Ease Of Usementioning
confidence: 99%
See 1 more Smart Citation
“…The ultimate reason that users exploit digital libraries is that they find the systems useful to their information needs or search tasks (Hong et al, 2002). Past researches Ramayah & Aafaqi, 2004;Davis, 1989;Mathieson, 1991;Adams et al, 1992;Segars & Grover, 1993, Igbaria, Iivari, & Maragahh, 1995Igbaria, Zinatelli, Cragg, & Cavaye, 1997;Ndubisi et al, 2001;Ramayah, Ignatius, & Aafaqi, 2002, Ramayah, Sarkawi, & Lam, 2003 has shown that PU influences computer usage directly. Hence, it is hypothesize that: …”
Section: Perceived Usefulnessmentioning
confidence: 99%